Designing a combined neonatal and obstetric air ambulance service: the birth of 'Airborn'. (18th April 2012) - Collins, SL; Bennett, C; Black, RS; Impey, L
Abstract : The combination of a perception of 'low risk' and professional pressures contribute to women travelling internationally throughout their pregnancy. If specialty care is required, mothers may find themselves in the 'wrong' place. We have developed the UK's first perinatal air ambulance service to support specialised aeromedical transfers. A review of reports involving air transport of obstetric patients was undertaken. The most common reasons for transfer were threatened preterm labour and preterm, prelabour rupture of membranes (PPROM). Nausea, vomiting and increased contractions were frequently reported in-flight complications. Few in-flight deliveries were reported. This was used to profile the equipment and drug requirements given the limited space available. The first combined neonatal and obstetric transfer was undertaken shortly after this. A UK citizen, 29 weeks into a 'low risk' pregnancy, was visiting Kazakhstan when her membranes ruptured. A team consisting of a neonatologist & obstetrician flew out. On arrival, the patient was septic and labouring. She was delivered by internal podalic-version and breech extraction after a shoulder presentation & cord prolapse. The baby was resuscitated, intubated and treated for sepsis. Less than 12 hours later they were in a UK hospital. Both are now at home and doing very well. This demonstrates that an NHS trust in collaboration with an established air ambulance service can provide a high quality perinatal transfer service for the rare occasions that it is needed. This speciality service is also ideally placed to provide rapid access to step up care within the centralised model of the NHS.